2001
DOI: 10.1046/j.0022-202x.2001.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Induction of Hair Growth by Dermal Cells Isolated from Hair Follicles After Extended Organ Culture

Abstract: Successful hair follicle organ culture has been established for some time, but hair growth in vitro is limited and generally terminates prematurely in comparison with in vivo. The reasons why growth stops in culture are as yet unknown. In this investigation, adult rat vibrissa follicles for which growth in culture is limited to about 10 d, were maintained in vitro for a minimum of 20 d after the hair shaft stopped growing. The pattern of fiber growth and long-term follicle pathology reflected the initial hair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…This observation confirms earlier histologic findings reported by Philpott and Kealey [2000] and Robinson et al [2001]. The possibility of this interesting feature was also proposed by Young and Oliver [1976], who suggested that 2 shafts can be present together in situations in which the regenerating shaft is rapidly growing before the degenerating shaft has left the follicle.…”
Section: Vibrissal Shaftsupporting
confidence: 80%
See 1 more Smart Citation
“…This observation confirms earlier histologic findings reported by Philpott and Kealey [2000] and Robinson et al [2001]. The possibility of this interesting feature was also proposed by Young and Oliver [1976], who suggested that 2 shafts can be present together in situations in which the regenerating shaft is rapidly growing before the degenerating shaft has left the follicle.…”
Section: Vibrissal Shaftsupporting
confidence: 80%
“…In other studies, the regenerating shaft was labeled as a 'growing whisker' [Young and Oliver, 1976] and as a 'new fiber' [Philpott and Kealey, 2000]. The degenerating shaft has previously been labeled a 'mature club' [Young and Oliver, 1976], a 'keratinized club hair' [Philpott and Kealey, 2000], and an 'elevated club fiber' [Robinson et al, 2001].…”
Section: Vibrissal Shaftmentioning
confidence: 99%
“…The induced hair follicles retain morphologic and hair cycle characteristics of the donor hair follicle (Reynolds and Jahoda, 1992). DP may also be placed in culture to increase cell numbers, which may then be implanted to induce hair follicle development (Jahoda and Oliver, 1981;1993;Messenger, 1984;Horne et al, 1986;Reynolds and Jahoda, 1992;Watson et al, 1994;Inamatsu et al, 1998;Robinson et al, 2001). In theory, this simple but eÂĄective method of tissue engineering may be employed to treat hair loss due to a variety of diseases, syndromes, and injuries and may provide signiÂącant insights into tissue and organ engineering.…”
mentioning
confidence: 96%
“…The tendency of aggregation is one of the significant properties of the DPC, and this property is associated with their biologic function and differentiating state [2][3][4][5][6]. Early passage dermal papilla cells have aggregative behavior and can induce hair growth in vivo, but, upon further culturing, this property is lost (Fig.…”
Section: Introductionmentioning
confidence: 97%